2020
DOI: 10.1142/s2010132520500200
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization and Analysis of Thermoacoustic Refrigerators

Abstract: Thermoacoustic refrigeration, a novel technology, uses eco-friendly gases like helium, air or the mixture of noble gases as working substances in the absence of moving parts. The design, optimization and analysis of thermoacoustic refrigerators using helium and air as oscillating gases are discussed. Pure helium is chosen since it is proven as the best and economical working gas compared to the alternate pure or the mixture of noble gases. Air is chosen since it is abundant in nature and the least cost of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In this section the design and optimization of the stack, cold and ambient heat exchangers having spiral geometry with 85% porosity to minimize acoustic field disturbances to improve cooler performance compared to 75% porosity is discussed [7,8]. The geometry and cross section of the stack and heat exchangers is same except the length.…”
Section: Design and Optimization Of Stack-heat Exchangers Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section the design and optimization of the stack, cold and ambient heat exchangers having spiral geometry with 85% porosity to minimize acoustic field disturbances to improve cooler performance compared to 75% porosity is discussed [7,8]. The geometry and cross section of the stack and heat exchangers is same except the length.…”
Section: Design and Optimization Of Stack-heat Exchangers Systemmentioning
confidence: 99%
“…It is found that the ambient heat exchanger rejects heat nearly twice the heat supplied by the cold heat exchanger [4,5,15]. Hence, (7) 2x 1 = 2P a sin(cx) ρuω the length of the ambient heat exchanger l 2 is equal to 2l 4 . The normalized critical temperature gradient Γ calculated for both helium and air for the four SLCC are found to be less than one (Table 6), confirms the spiral stack behaves as refrigerator [4,5,13,[15][16][17].…”
Section: Table 3 Normalized Design Parameters Of Thermoacoustic Refri...mentioning
confidence: 99%
See 3 more Smart Citations